2008
DOI: 10.1208/s12249-008-9130-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-built Supercritical CO2 Anti-solvent Unit Design, Construction and Operation using Carbamazepine

Abstract: Abstract. The purpose of this study was to design and build a supercritical CO 2 anti-solvent (SAS) unit and use it to produce microparticles of the class II drug carbamazepine. The operation conditions of the constructed unit affected the carbamazepine yield. Optimal conditions were: organic solution flow rate of 0.15 mL/min, CO 2 flow rate of 7.5 mL/min, pressure of 4,200 psi, over 3,000 s and at 33°C. The drug solidstate characteristics, morphology and size distribution were examined before and after proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…43 Supercritical anti-solvent method was used to prepare CBZ microparticles of 200-400 mm. 44 Sub-micron sized particles of CBZ were produced using spontaneous emulsication process 45 and rapid expansion of supercritical solution (RESS) method. 46 Chitosan solid lipid nanoparticles of CBZ with particles size 158-170 nm is also reported.…”
Section: Introductionmentioning
confidence: 99%
“…43 Supercritical anti-solvent method was used to prepare CBZ microparticles of 200-400 mm. 44 Sub-micron sized particles of CBZ were produced using spontaneous emulsication process 45 and rapid expansion of supercritical solution (RESS) method. 46 Chitosan solid lipid nanoparticles of CBZ with particles size 158-170 nm is also reported.…”
Section: Introductionmentioning
confidence: 99%
“…The systems studied using this method were indomethacin (IND), carbamazepine (CBZ), nonsteroidal anti-inflammatory drugs (NSAIDs), and theophylline (TPL), a bronchodilator. Other authors already processed these molecules by SAS, resulting in polymorphs, which provides a motivating background for discussion. ,,,, A computational fluid dynamics (CFD) model previously developed by Rodrigues et al was further adapted herein to simulate supersaturation and provide better insight into what is happening in the ASAIS mixing chamber. Several operating conditions associated with ASAIS processing, such as pressure, initial concentration of solution, liquid flow, and nozzle diameter were explored to understand the mechanisms involved in the formation of polymorphs by scCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies that have considered the effects of density and diffusivity of a SCF and PGSS method and the relationship with yield and in vitro dissolution, and no studies have determined the effects of different SCF conditions on the formation of PGN-loaded Gelucire 44/14 dispersion systems. In one study, the SCF conditions were examined in the formation of carbamazepine particles using a GAS method using 290 bar at 33°C produced the highest yields (73%), while lower temperatures yielded little or nothing (39). Another study showed that nifedipine can be processed using a PGSS-CO 2 , and depending on the SCF conditions, the nifedipine dissolution rate was significantly increased by approximately double after 15-60 min (40).…”
Section: Discussion Effect Of Pressure (A) and Temperature (B) Of Sc-mentioning
confidence: 99%